Prospects of Agro Forestry in Rupnagar District of Punjab, India - Ghuman, R. S.; Singh, Harinder; Singh, Paramdeep (International Journal of Economic Plants, 2017)
Agroforestry systems provide a number of ecosystem services and environmental benefits besides being a viable land-use option and a source of additional income for the farmers. A survey was carried out in the Chamkaur Sahib block of Rupnagar district of Punjab to review about the agroforestry related practices followed by the local farmers and to identify the knowledge gaps. 50 farmers were surveyed randomly and incidentally all were practicing agroforestry. A set questionnaire was asked from them and the information generated through this survey is shared in this paper.